Dinamika pengelolaan wakaf uang: studi sosio-legal perilaku pengelolaan wakaf uang pasca pemberlakuan UU No. 41 tahun 2004 tentang wakaf - Hilmi, Hasbulah (IJTIHAD Jurnal Wacana Hukum Islam dan Kemanusiaan, 2012)
The reality of the implementation of cash waqf after regulation Act No. 41 in 2004 on Waqf studied to address the problem: how cash waqf be understood accepted and implemented by the cash waqf institutions; and how cash waqf be managed by cash waqf institutions in Indonesia? The study is a socio-legal study with phenomenological qualitative research methods. This study focus on understanding the cash waqf regulation as âlaw in the bookâ and how the implementation and acceptance of cash waqf as a âlaw in the societyâ. Social and law change, and behavior and effectiveness of law theories are used as a research perspective The findings of this study are as follows. Firtsly, It is founded that understanding and acceptance levels of cash waqf regulations is various. The various is acceptance and using all of cash waqf regulation, using a part and totally avoidance and ignorant the regulation. Secondly, Cash waqf regulation delegitimize the cash waqf process has been developed by the community. It is impact to avoid or ignore the regulation by most of waqf board and foundations. Some foundations avoid the regulation and switch to the model of other charitable. The others ignore the regulation and keep up with the concept of cash waqf has been understood. The avoidance and ignorant foundations earn the trust (even likely to increase) of the people. The other side the development of cash waqf management as the regulation is less encouraging. It is show that waqf act especially on cash waqf regulation is less effective.